Secure AdHoc on demand distance vector routing protocol using media access control and symmetric encryption against black hole and DDoS attacks in manet - Khan, Samia (2018)
The Mobile Ad hoc Network (MANET) is an infrastructureless network that has applications in many fields. MANETs can change locations and configure themselves on the fly; the nodes are self-configuring and able to self-organize. For data communication, nodes in the MANETs act as router to forward data packet to other nodes in the network. To communicate in the network, the nodes need routing protocol to establish a route and exchange the data in a secure way. Ad hoc On Demand Distance Vector (AODV) is one of the frequently used routing protocols due to its reactive nature advantage. Nevertheless, AODV has the disadvantage of being attacked by various types of attacks, specifically black hole attacks and Distributed Denial of Service (DDoS) attacks where it publicizes itself by announcing that it has the shortest path to the destination by altering the important routing parameters. These threats are difficult to handle because of their characteristics, like the huge scale of botnets and the dynamic nature of attacking, which constitutes a DDoS attack. DDoS attacks should be handled and mitigated directly from the network as early as possible. Many researchers have come up with a number of research work for defending against these attacks. However, most of these solutions lead to the increase in routing overhead which affects the overall performance of the network. The main challenge in MANETs is to come up with a secure routing protocol that is lightweight and whose implementation results in less overhead, better performance and a secure network. For that reason, a lightweight defense mechanism that can secure the network from the attackers is resourceful as the cooperation between the neighbouring nodes is counted in MANETs. This research focuses mainly on a defense against the Black Hole and DDoS attacks which involves two authentication levels: a) layer-2 authentication, and b) symmetric encryption on the control packets to secure the established path from AODV routing before exchanging the data. This is done by modifying the conventional AODV routing protocol. The primary focus of this approach is the sub layer that is layer 2 of the Open Systems Interconnections model (OSI), which uses the Media Access Control (MAC) authentication for checking the validation and authenticity of the nodes that want to participate in the network. Both routing information and the MAC information are specifically checked for securing the network. The solution is implemented in the AODV protocol and tested on various scenarios in order to achieve the optimum results. The trace file which is the output from the Network Simulator 2 (NS2) shows better improvement over existing approaches. The analysis shows good network performance with maximum average throughput of 96.5% and reduced routing overhead of 4.71%, offering true positive detection rate at maximum value of 92%. Moreover, this proposed solution endeavours higher packet delivery ratio with relatively less end to end delay (EED) when compared to two recent research works (LSAM and HMAC).